From Theory to Practice: Funds of Knowledge as a Framework for Science Teaching and Learning - St. Clair, Tyler; McNulty, Kaitlin (Innovations in Science Teacher Education, 2021)
The phrase "funds of knowledge" refers to a contemporary science education research framework that provides a unique way of understanding and leveraging student diversity. Students’ funds of knowledge can be understood as the social relationships through which they have access to significant knowledge and expertise (e.g., family practices, peer activities, issues faced in neighborhoods and communities). This distributed knowledge is a valuable resource that might enhance science teaching and learning in schools when used properly. This article aims to assist science methods instructors and secondary classroom teachers to better understand funds of knowledge theory and to provide numerous examples and resources for what this theory might look like in practice.